Bridging the Gap: From Homogeneous to Heterogeneous Parahydrogen‐induced Hyperpolarization and Beyond. Issue 8 (6th April 2021) - Chekmenev, Eduard Y.; Goodson, Boyd M.; Bukhtiyarov, Valerii I.; Koptyug, Igor V.
Abstract: Demonstration of parahydrogen‐induced polarization effects in hydrogenations catalyzed by heterogeneous catalysts instead of metal complexes in a homogeneous solution has opened an entirely new dimension for parahydrogen‐based research, demonstrating its applicability not only for the production of catalyst‐free hyperpolarized liquids and gases and long‐lived non‐equilibrium spin states for potential biomedical applications, but also for addressing challenges of modern fundamental and industrial catalysis including advanced mechanistic studies of catalytic reactions and operando NMR and MRI of reactors. This essay summarizes the progress achieved in this field by highlighting the research contributed to it by our colleague and friend Kirill V. Kovtunov whose scientific career ended unexpectedly and tragically at the age of 37. His role in this research was certainly crucial, further enhanced by a vast network of his contacts and collaborations at the national and international level. Abstract : Scientific achievements of Kirill Kovtunov, our talented young colleague and friend whom we lost in 2020, include the first demonstration of parahydrogen‐induced polarization of nuclear spins in hydrogenations over heterogeneous catalysts such as immobilized metal complexes and supported metals, an important step toward production of catalyst‐free hyperpolarized liquids and gases for both biomedical applications and modern catalysis research.